Impact of perceived social support and parental bonding in predicting suicidal intent among self-harm patients - Naila Yaqoob; Sadaf Ahsan (Journal of the Pakistan Medical Association, 2021)
Objective: The present study investigated the impact of perceived social-support and parental-bonding in predicting suicidal intent among self-harm patients. Methods: Cross-sectional research design was used in current study. Study was conducted at Foundation University, Rawalpindi from February, 2019 to September, 2019. A purposive sample of 50 self-harm patients was collected from different mental health departments of hospitals of Rawalpindi, Jhelum and Peshawar. Participants were administered Multidimensional Scale of Perceived Social Support (MSPSS), Parental-Bonding Instrument (PBI) and Beck Suicide Intention Scale (BSIS). Data was analyzed through SPSS using correlation, t test and regression. Differences on the basis of demographic variable were also studied. Results: The main results of the study specified that social support and parental bonding’ factor ‘care’ had significant negative correlation with suicide intent. Moreover, it negatively predicted suicide intent. Whereas, parental boding’ factor ‘overprotectiveness’ had significant positive correlation with suicide intent and significantly positively predicted suicide intent. Conclusion: The outcomes of present study emphasized that social-support and parental bonding both can play substantial roles in saving lives. Researchers and mental health experts will be able to start examine about the factors that distinguish deliberate self-harm from attempted suicide as well as the characteristics common to both conducts. Continuous...